ChemInform Abstract: Biomaterials Based Nano‐Applications of Aloe vera and its Perspective: A Review. Issue 50 (December 2015) - Balaji, Arunpandian; Vellayappan, Muthu Vignesh; John, Agnes Aruna; Subramanian, Aruna Priyadarshini; Jaganathan, Saravana Kumar; SelvaKumar, M.; Faudzi, Ahmad Athif bin Mohd; Supriyanto, Eko; Yusof, Mustafa
Abstract: Review: 118 refs.